Self-efficacy as a mediator of the influence of education and entrepreneurial motivation on students’ entrepreneurial interest - Oey Hannes Widjaja; Lianah The; Johnathan Susanto; Christofer Andre William (Universitas Muhammadiyah Enrekang, 2025)
The purpose of this research is to examine effect Entrepreneurship Education and Entrepreneur Motivation on Entrepreneurial Interest and examine Self Efficacy as a mediator of Entrepreneurship Education and Entrepreneur Motivation on Entrepreneurial Interest. The population of this research is Student At The University Of Tangerang. The population used in this research was 182 valid respondents. This research uses the Non-Probability Sampling method with the Purposive Sampling method to collect online via g-form and then process using smartPLS-SEM. The results of this research are that Entrepreneurship Education and Entrepreneur Motivation can affect Entrepreneurial Interest, Entrepreneurship Education and Entrepreneur Motivation can affect Self Efficacy and Self Efficacy can mediate Entrepreneurship Education and Entrepreneur Motivation on Entrepreneurial Interest